La inclusión escolar - Morales Quishpe, Luis Diego (2016)
The project presented aims to investigate the school inclusion and how it affects the educational community, including in our country has been considered a breakthrough in education and that the Constitution, LOEI, CONADIS, BASIC LAW. He speaks of guaranteed and equal education for all, education is a right of people throughout their lives and an unavoidable and inexcusable duty of the State. That is why the project developed aimed to develop a methodological guide inclusive for teachers in the educational unit "Luis Fernando Vivero" strategies, taking into account people with disabilities, race, religion, and discriminated against by others, and who they have difficulty develop in their educational environment. This work was carried out based on the results of the application of research techniques and instruments such as interview and survey teachers who allowed us to establish the respective conclusions and recommendations of this work; also it includes a theoretical framework school inclusion, its importance, advantages and disadvantages that lead to propose solutions to the problem identified, allowing reflect why this research, and the feasibility of it is described. Inclusion is a process that aims to introduce all members of the school community where all children are integrated within an institution with disabilities in this way, in which we rely on legal approaches, psychological, psychophysical in the same way we focus on the different disabilities, motor, sensory, auditory, diseases visual there are also diseases multireto disability this tells us that a student may have beyond a disability and identify and respond to the diverse needs of all students through increased participation in learning, and reducing exclusion in education.